Pengaruh Kemudahan, Keamanan, Resiko Dan Promosi, terhadap Keputusan Penggunaan Shopee Paylater Di Solo Raya - Rizqi Akbar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of convenience, security, promotion risks on the decision to use shopee paylater in Solo Raya. This research is a quantitative study, the population used is shopee paylater users who are in Solo Raya. Sampling in this study used purposive sampling techniques totaling 97 respondents. The data of this study were taken using a questionnaire. Meotde data analysis used validity and reliability tests, classical assumption tests and multiple linear regression tests using the spss23 program. The results of this study show that partially convenience does not have a significant effect on usage decisions, while security, risk, promotion, have a significant positive effect on usage decisions.